Synthesis of Sulfonylhydrazine-1,2-dicarboxylates from Thiols and Dialkyl Azodicarboxylates - Zhou, Bingnan; Yang, Xiao; Xu, Jiaxi (Synthesis, 2017)
1-Sulfonylhydrazine-1,2-dicarboxylates are efficiently prepared via nucleophilic addition of thiols/thiophenols to dialkyl azodicarboxylates and subsequent oxidation with MCPBA. The protocol represents the first application of sulfenylhydrazines as precursors to sulfonylhydrazine derivatives, leading to a novel and effective method for the synthesis of sulfonylhydrazines.
Keywords: MCPBA; sulfenylhydrazines; sulfonylhydrazines; oxidation; addition; azodicarboxylates; thiols; thiophenols